2007
DOI: 10.1080/00926230701267886
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Functioning and Partner Relationships in Women with Turner Syndrome: Some Empirical Data and Theoretical Considerations Regarding Sexual Desire

Abstract: The aim of this study was to describe marital status, sexual history, and sexual functioning in a group of women with Turner syndrome, and to compare the results with general Swedish population data. The sample consists of 57 women over 18 years of age. Data were collected from an interview, and using two self-report questionnaires: the McCoy Sexual Rating Scale and the Relationship Rating Scale (RS). Compared to population data, the women with Turner syndrome were less likely to have a partner and had had the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
28
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 26 publications
4
28
0
Order By: Relevance
“…These results are in agreement with other studies, which demonstrated that TS subjects in a partner relationship reported relatively normal overall sexual function, but those without partners declared very low-level sexual functioning. 12,28 Conversely to TS subjects, large differences were encountered when comparing OCH women with controls in most of the domains and in total score. These results could be interpreted as an important complaint of these patients regarding their sexual life, and although HRT is standard for women with premature ovarian failure at age Ͻ50 years, pharmacological hormone regimens do not fully mimic natural steroids production.…”
Section: Wwwajogorgmentioning
confidence: 63%
“…These results are in agreement with other studies, which demonstrated that TS subjects in a partner relationship reported relatively normal overall sexual function, but those without partners declared very low-level sexual functioning. 12,28 Conversely to TS subjects, large differences were encountered when comparing OCH women with controls in most of the domains and in total score. These results could be interpreted as an important complaint of these patients regarding their sexual life, and although HRT is standard for women with premature ovarian failure at age Ͻ50 years, pharmacological hormone regimens do not fully mimic natural steroids production.…”
Section: Wwwajogorgmentioning
confidence: 63%
“…Women with TS seem more likely to be delayed in achieving adult sexual and social developmental milestones compared with norms. 11 Research with young adults with TS has shown a self-perception of poor social competence among women with mixed TS karyotypes when compared with controls, and of greater withdrawal from peer-interactions among women with 45,X karyotypes compared with other karyotypes. 12 Women with TS, along with karyotypically normal women with premature ovarian failure, have also reported heightened levels of shyness, social anxiety, depression, and decreased self-esteem in comparison with healthy women.…”
Section: Psychosocial Skills Are Commonly Impaired In Turner's Syndromementioning
confidence: 98%
“…Women with TS move away from home later, are older at sexual debut compared to average population reference data (206,452,453) and show impaired sexual function particularly relating to arousal (454). They should have access to a gynecologist experienced in ovarian insufficiency in young women.…”
Section: Sexual Function In Adultsmentioning
confidence: 99%